2000
DOI: 10.1007/s004200000157
|View full text |Cite
|
Sign up to set email alerts
|

Air and biological monitoring of solvent exposure during graffiti removal

Abstract: Many different cleaning agents were used. The average exposure to solvents was low, but some working tasks included relatively high short-term exposure. To prevent adverse health effects, it is important to inform workers about the health risks and to restrict the use of the most toxic chemicals. Furthermore, it is important to develop good working procedures and to encourage the use of personal protection equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 8 publications
3
37
2
4
Order By: Relevance
“…Occupational exposure to mixtures of organic solvents has been evaluated in many activities, such as painting, paint spraying, floor-laying, shoe making, laundries, graffiti removers, etc [13][14][15][16] . Several studies have focused on car repair painters, since this class of workers usually suffers of long-term exposure to relatively high levels of many different solvents 2,17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure to mixtures of organic solvents has been evaluated in many activities, such as painting, paint spraying, floor-laying, shoe making, laundries, graffiti removers, etc [13][14][15][16] . Several studies have focused on car repair painters, since this class of workers usually suffers of long-term exposure to relatively high levels of many different solvents 2,17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…In a study where Swedish graffiti removers working with NMP-containing cleaning agents, dermal absorption was suggested to play an important role on the development of irritation (Anundi et al, 2000). Furthermore, the importance of the dermal absorption have been showed in studies where rats exposed head only to 1000 mg NMP/m 3 only showed irritation to the respiratory system, while whole body exposure to the same concentration, caused severe effects on major organs and an extensive mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Dermal exposure was suggested to play an important role in a study performed Åkesson et al on 38 Swedish graffiti removers using cleaning agents containing NMP (13).…”
mentioning
confidence: 99%